2017
DOI: 10.1002/jcla.22336
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation of a multiparametricELISAas a rapid tool for routinely diagnosing IgG‐mediated autoimmune blistering dermatoses in ethnic Slavs

Abstract: Multivariant ELISA test combined with clinical examinations and DIF is recommended as a minimal approach to diagnosing ABDs in ethnic Slavs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Our case was diagnosed with a combination of imaging and biochemical-molecular techniques. The DIF visualised with the blue light-emitting diode technology-operated microscopy for patterning of IgG4 and IgG1 deposits along the DEJ in perilesional tissue combined with the multiplex ELISA detecting serum IgG antibodies to BP180 and/or BP230 is an approach advocated by us for routine differential laboratory diagnostics of BP in our native population ( 11 , 12 ). Usually, we detect IgG4, but not IgG1 deposits with DIF in BP, nevertheless in our case IgG1, but not IgG4, deposits were detected ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our case was diagnosed with a combination of imaging and biochemical-molecular techniques. The DIF visualised with the blue light-emitting diode technology-operated microscopy for patterning of IgG4 and IgG1 deposits along the DEJ in perilesional tissue combined with the multiplex ELISA detecting serum IgG antibodies to BP180 and/or BP230 is an approach advocated by us for routine differential laboratory diagnostics of BP in our native population ( 11 , 12 ). Usually, we detect IgG4, but not IgG1 deposits with DIF in BP, nevertheless in our case IgG1, but not IgG4, deposits were detected ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…Still, there are cases of malignancy-associated PV without laboratory features of PNP. A multiplex ELISA containing envoplakin combined with a clinical examination and a DIF should be helpful for routine laboratory diagnostics and differentiation of PNP [ 22 ].…”
Section: Case Report: Ocular Involvementmentioning
confidence: 99%
“…Recent studies showed that the sensitivity and specificity of BIOCHIP and ELISA in pemphigus diagnostics and type differentiation are comparable [ 11 ]. Both BIOCHIP and the recently used multiparametric ELISA allow for quick, one-step and simultaneous identification of autoantibodies directed against various antigens in several sera, which is particularly useful in patients with an unusual clinical picture and convenient for use in small laboratories [ 12 , 13 ]. Routinely, immunoblot and immunoprecipitation are rarely used [ 14 ].…”
Section: Pemphigus Groupmentioning
confidence: 99%